Peran Pendidikan Pancasila Dalam Mewujudkan Nilai-Nilai Keislaman Bangsa Indonesia - Moh. Nor Abrori (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the role of Pancasila Education in the internalization of Islamic values in Indonesia amid the challenges of globalization that influence the character of the younger generation. This research employs a qualitative approach using a library research design, focusing on the examination of concepts, theories, and empirical findings from various scientific sources. Data collection techniques were conducted through documentation studies of scientific journals, reference books, and relevant policy documents. The data were analyzed using descriptive qualitative analysis through the stages of data reduction, data display, and conclusion drawing. The results indicate that there is a substantial alignment between the values of Pancasila and Islamic values, such as divinity, humanity, unity, deliberation, and social justice. The internalization of these values can be carried out through contextual learning, teacher role modeling, and habituation within the educational environment. However, the implementation still faces several challenges, including the dominance of cognitive-based approaches, limited teacher understanding in integrating values, and insufficient supportive environments. These findings contribute to enriching the discourse on character education based on the integration of ideological and religious values. Practically, this study emphasizes the importance of developing integrative and reflective learning strategies in Pancasila Education. Policy implications include strengthening the curriculum and improving teacher competencies. Future research is recommended to employ field-based approaches to gain deeper empirical insights into the process of value internalization in educational practices.